Some Structural and Thermal Characteristics of Snow Shelters - Elsner, Robert W.; Pruitt, Jr., William O. (ARCTIC, 1959)
Reports investigations of dome-shaped shelters constructed in Alaska during winter 1955-56, some of loose, unconsolidated snow at the Arctic Aeromedical Laboratory, near Fairbanks, others of snow blocks on sea ice at Barter Island (70 08 N, 143 40 W). Pneumatic forms such as inflated weather balloons were useful, but not indispensable, in the loose snow type. Due to compaction, the density of the snow increased during construction from 0.22 gm/cu cm to 0.28 gm/cu cm and the hardness range from 8-80 gm/sq cm to 200-850 gm/sq cm Air temperatures in and outside both occupied and unoccupied shelters of this type (tabulated) demonstrate the efficacy of snow as an insulator and thermal advantages derived from ground heat. Inside temperature close to that at the ground surface, remained nearly constant (15-20 F) while outside temperatures ranged from -12 to -40 F Shelters were warmer during occupancy. In the snow-block shelters built on bare sea ice and on an 18 in deep drift, temperatures varied from 10-19 F at the top, 7-20 F in the center, and 7-18 F at the floor, while outside temperatures ranged from -2 to -5 F; thus subnivean warmth on sea ice can also be utilized. The temperature in a 2.5 ft deep trench in a drift, covered with a roof of horizontal snow blocks, was 20-24 F at the sleeping level 6 in above the floor.